2011
DOI: 10.1093/glycob/cwr188
|View full text |Cite
|
Sign up to set email alerts
|

Glycosides of hydroxyproline: Some recent, unusual discoveries

Abstract: Glycosides of hydroxyproline (Hyp) in the plant cell wall matrix were discovered by Lamport and co-workers in the 1960s. Since then, much has been learned about these Hyp-rich glycoproteins. The intent of this review was to compare and contrast some less common structural motifs, in nontraditional roles, to uncover themes. Arabinosylation of short-peptide plant hormones is essential for growth, cell differentiation and defense. In a very recent development, prolyl hydroxylase and arabinosyltransferase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Extensins also have been implicated in cell elongation (Velasquez et al, 2011;Taylor et al, 2012;Nguema-Ona et al, 2014). Although less pronounced than for XyG, we also observed a polarized distribution of extensin epitopes recognized by the mAbs LM1, LM3, and JIM20 (Fig.…”
Section: Xyg and Extensin Epitopes Display Polarized Distribution Witmentioning
confidence: 51%
“…Extensins also have been implicated in cell elongation (Velasquez et al, 2011;Taylor et al, 2012;Nguema-Ona et al, 2014). Although less pronounced than for XyG, we also observed a polarized distribution of extensin epitopes recognized by the mAbs LM1, LM3, and JIM20 (Fig.…”
Section: Xyg and Extensin Epitopes Display Polarized Distribution Witmentioning
confidence: 51%
“…In addition, recent work has found that proteins may be phosphorylated and glycosylated on hydroxyproline residues, suggesting a richer range of post-translational modifications accessible in this residue. 22 In order to address these questions, both 4 R and 4 S diastereomers of hydroxyproline were modified to the phosphorylated and to the diethylphosphate triester forms (Scheme 14, 97 - 100 ). Notably, phosphorylation ionization state changes as a function of pH, and therefore the structure of peptides with phosphorylated hydroxyproline could change as a function of pH.…”
Section: Resultsmentioning
confidence: 99%
“…Plant O -glycosylation differs significantly from mammals as plants do not have a functional mucin-type O -glycosylation pathway ( Castilho et al, 2012 ; Yang et al, 2012 ). Plants, on the other hand, can convert proline residues adjacent to O -glycosylation sites into hydroxyproline (Hyp; Taylor et al, 2012 ). Serine residues next to specific Hyp-sequence motifs may be modified with single galactose and Hyp residues and can be extensively modified with arabinose chains or arabinogalactans ( Seifert and Roberts, 2007 ; Basu et al, 2013 ; Saito et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%